Social Impacts of Climate Change in Chile : A Municipal Level Analysis of the Effects of Recent and Future Climate Change on Human Development and Inequality - Andersen, Lykke E.; Verner, Dorte (World Bank, Washington, DC, 2014)
This paper uses municipality level data to estimate the general relationship between climate, income, and life expectancy in Chile. The analysis finds that incomes are negatively related to temperature, while life expectancy is not significantly related to average temperatures. Both incomes and life expectancy are greater in areas with either very little rain or a lot of rain. The authors use the estimated relationships to simulate the effects of both past (1958-08) and future (2008-58) climate change. The findings indicate that past climate change has been favorable for the central, and most populous, part of Chile, and it has contributed to reduced poverty and reduced inequality of health outcomes. Whereas temperatures in the past have shown a downward trend for most of the Chilean population, climate models suggest that they will increase in the future, and that there will be a reduction in precipitation in the central part of Chile. The analysis simulates the likely effects of these projected climate changes over the next 50 years. The findings suggest that expected future climate will tend to reduce incomes across the whole country, with an average reduction of about 7 percent, all other things equal.